Josiah Wedgwood : 'the Arts and Sciences United'. - des Fontaines, John; Science Museum London; Chaldecott, John; Tindall, John (Barlaston : Josiah Wedgwood & Sons, 1978)
portret van Josiah Wedgwood als kunstenaar en wetenschapper
Adlib record nr. 530008623
Engels
Josiah Wedgwood: 'the Arts and Sciences United'
kunstcatalogus
Keywords: Wedgwood, Josiah; Wedgwood; 1730 - 1795; Groot-Brittannië (Engeland)